Strategi Pengembangan Ekowisata sebagai Produk Pariwisata Berkelanjutan di Desa Karya Sari, Kabupaten Tabanan - Sukariyanto, I Gede Made; Susila, I Made Gede Darma (Journal of Applied Science in Tourism Destination, 2023)
With post-pandemic conditions becoming more conducive, tourism activities are also gradually returning to a normal position. Experience during the pandemic has changed the mindset of tourists towards tourist destinations, where in the next normal period, tourists are predicted to prefer destinations for "healing" that are nature-based and also support a healthier life. Karya Sari Village in Tabanan Regency has the potential to support this tourism trend by implementing the ecotourism concept in its development. The purpose of this study is to develop a tourism product development strategy based on the concept of ecotourism in Karya Sari Village. Research design used in this study is a qualitative approach, where data is collected through purposive sampling, by conducting in-depth interviews with local tourism management (pokdarwis) and village officials. The results of the study show that Karya Sari Village has superior tourism products, which are feasible to be packaged with the concept of ecotourism. Interestingly, even though the village does not have a legal status of a Tourism Village, with good opportunities Karya Sari Village is currently in quadrant I based on IFAS EFAS analysis, so that managers can implement aggressive strategies in developing ecotourism products. local tourism management (pokdarwis) is recommended to increase village promotion and brand awareness as well as conducting more research to examine the concept of sister village development.